Estimating the Shear-Wave Velocities of Shallow Sediments in the Yellow Sea Using Ocean-Bottom-Seismometer Multicomponent Scholte-Wave Data - Wang, Yuan; You, Qingyu; Hao, Tianyao (Frontiers in Earth Science, 2022)
Scholte-wave dispersion analysis is effective at imaging the relatively low shear-wave velocity of shallow marine sediments in marginal seas. The combination of a four-component ocean-bottom-seismometer (OBS) and a towed air-gun source can economically and effectively acquire the marine dispersive seismic data. Extracting higher-order dispersive Scholte wave modes is the most critical problem in the dispersion analysis method. The extremely low shear-wave velocity and severe attenuation in the top hundreds of meters of marginal sea sediment provide an uneven dispersive energy distribution for the four components of the Scholte wave data. The fundamental mode dispersive energy dominates in the vertical component and higher-order modes dominate in the horizontal component. We developed the method of the four-component OBS Scholte velocity-spectra stacking, which can effectively, rapidly, and robustly extract higher-order modes. We imaged the shear-wave velocity structure of complicated shallow marine sediment in the North Yellow Sea using an active OBS seismic profile with a large-volume air-gun array. The fourth higher-order Scholte wave mode can be imaged with the four-component velocity-spectra stacking method with a lower frequency range of 1.0–7.0 Hz. Only the second-order mode can be recognized from the dispersion energy image of the single vertical component. The joint inversion of multimode dispersion curves can provide more accuracy and deeper constraints for the inverted model; thus, the constraint depth with five modes increases by a factor of 1.9 compared with single fundamental mode inversion. The inverted profile suggests a low shear-wave velocity of 123–670 m/s and strong lateral variations within 350 m. The main regional geological structures are shown by the inverted shear-wave velocity structure.